Review Identifikasi Risiko Atas Pipa yang Terkubur di Bawah Jalur Kereta Api (Politeknik Perkeretaapian Indonesia Madiun, 2023)
The presence of pipes beneath railway lines poses potential risks and hazards to railway operations. Identification of the risks arising from pipes located under railway lines is necessary for evaluation and preparation of strategic measures to reduce the level of risk. Risks to be aware of include pipe deformation, corrosion, design and installation errors, and operating errors. To ensure safety, pipe monitoring and inspection must be conducted regularly. Pipe inspection also needs to consider geotechnical elements to ensure that railway infrastructure remains safe for operation. This paper reviews several published studies and standards related to the safety of pipelines under the railways and summarizes the potential failures of pipelines located beneath railway tracks, various aspect of pipelines and railway safety, and the standards that can be used as references in designing pipelines buried beneath railway tracks